Gestantes atendidas no setor de DST - UFF em 1995 - Passos, Mauro Romero Leal; Tibúrcio, Alberto Saraiva; Tavares, Rogério Rodrigues; Stadnick, Celia Maria Pedrosa; Pinheiro, Vandira Maria dos Santos (Brazilian Journal of Sexually Transmitted Diseases, 1998)
Sexually transmitted disesases are frequently diagnosed among pregnant women. ln 1995, 34 (4.9%) of 694 new female pacients at rhe STD Sector of the Fluminense Federal University in Niterói, Brazil, were pregnanr. 28 (82,3%) of chese had STDs. HPV infection was the most common diagnosis.followed by vaginosis. Many among che pregnant women were teenagers or housewives with low education and income leveis. Most had a single exclusive partner. The author emphasize the importance of well supervised pre-natal exams to allow for early detecrion and tratament of these infections